The art of action research in the classroom - MacIntyre, Christine (London : D. Fulton Publishers, 2000)
Based on the experiences of teachers using action research with their pupils for the first time, this introductory text demystifies the issues commonly faced by the novice researcher. The author explains how the principles of action research can be effectively applied; how small-scale classroom research can discover important cues to aid learning; how to implement action research in different curricular areas, individually or in groups, and with children of different abilities; and how the whole endeavour can be structured to form an undergraduate or postgraduate thesis. Suitable for use in nu.
Includes bibliographical references
Keywords: Action research in education